2009 34th IEEE Photovoltaic Specialists Conference (PVSC) 2009
DOI: 10.1109/pvsc.2009.5411173
|View full text |Cite
|
Sign up to set email alerts
|

Modification of textured silicon wafer surface morphology for fabrication of heterojunction solar cell with open circuit voltage over 700 mV

Abstract: Crystalline silicon wafer (c-Si) can be extremely well passivated by plasma enhanced chemical vapor deposited (PECVD) amorphous silicon (a-Si:H) films. As a result, on flat substrates, solar cells with very high open circuit voltage are readily obtained. On textured substrates however the passivation is more cumbersome, likely due to the presence of localized recombinative paths situated at the pyramid valleys. Here, we show that this issue may be resolved by selecting a silicon substrate morphology featuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 11 publications
(9 reference statements)
4
16
0
1
Order By: Relevance
“…11) No microcrystalline and epitaxial crystal silicon growth occurs at the bases of the pyramids. 9) A similar crystallization pattern could occur in the present study. Therefore, the observed current grain in Fig.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…11) No microcrystalline and epitaxial crystal silicon growth occurs at the bases of the pyramids. 9) A similar crystallization pattern could occur in the present study. Therefore, the observed current grain in Fig.…”
supporting
confidence: 90%
“…8) Fesquet reported that the carrier lifetime increased in proportion to the size of the pyramidal texture, and that V oc could be increased by reducing the sharpness of the pyramids as well as the sub-micron pyramid density using isotropic etching. 9) In the pyramid valleys, the lm is not conformal, and epitaxial growth occurs. 9) Of equal morphological importance but much less investigated are the ridge lines of the pyramidal texture.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is verified by scanning electron microscopy (SEM) done before and after SC-15 treatment. The surface morphology doesn't change as the solution was not concentrated enough and the temperature wasn't high enough to round off the peaks of the random pyramids that has been typically shown in previous literature 9, 10 due to different isotropic etches for heterojunction cell processing. The diluted solution has a composition of 0.05 to 10% by weight water soluble alkanolamine, 0.01 to 2.5% by weight of quaternary ammonium hydroxide, 0.01 to 2% by weight chelating agent, and the pH of this composition is about 10 to 13.…”
Section: Methodsmentioning
confidence: 91%
“…Concerning the front side, different texturization techniques, anti‐reflective coatings (ARCs) depositions, and front surface field (FSF) formation processes have been proposed to reduce both optical and recombination losses. As a matter of fact, the analysis of novel texturing processes in high‐efficiency solar cells has been elucidated . On one hand, in fact, some papers have shown clear improvements in case of pyramid‐textured or nano‐textured structures mainly because of a reduction of front‐side optical losses .…”
Section: Introductionmentioning
confidence: 99%